Manajemen Pendidikan Islam di Madrasah Ibtidaiyah untuk Peningkatan Mutu Pembelajaran di Nganjuk - Yuniasari, Fenni (ALSYS, 2025)
The limited comprehensive studies on the application of modern management functions in the context of Madrasah Ibtidaiyah (MI), particularly in regional areas, contribute to the persistent quality gap between madrasahs and public schools. This study aims to provide an in-depth description of the implementation of Islamic education management, encompassing planning, organizing, implementation, and supervision, across several MIs in Nganjuk Regency. A qualitative approach was employed using a multi-case design involving three MIs selected based on variations in accreditation status and institutional reputation. Data collection techniques included interviews, participatory observations, and document analysis, while data were analyzed using the interactive model developed by Miles, Huberman, and Saldana. The findings indicate that planning remains reactive and lacks a strategic orientation; organizing is suboptimal, particularly in role distribution and teacher professional development; implementation relies heavily on individual teacher initiative, unsupported by a robust managerial system; and supervision tends to be formalistic, with minimal impact on quality improvement. The study concludes that enhancing learning quality in MI is highly dependent on the transformation of madrasah principals into visionary instructional leaders. These findings underscore the importance of leadership training, strengthened academic supervision, and the adoption of data-driven management as a foundation for effective decision-making within madrasahs.